Utility of aripiprazole in co-occurring problem gambling and toluene dependence: A case report. (4th March 2019) - Modak, Tamonud; Bhad, Roshan; Rao, Ravindra
ABSTRACT: Inhalant use is a global problem but in spite of its large prevalence and significant physical and psychological complications, there is inadequate literature on the management of inhalant dependence. Inhalants are also considered a substance of adolescence with most users giving up use in adulthood. There is also limited literature on co-occurring behavioral and substance addictions and the linkage between them. We describe the case of 28-year-old man who had been using toluene in a dependent pattern for 14 years. He also had problem gambling in the past, abstaining from which led to an increase in the daily quantity of use of toluene. The patient was tried on Carbabmazepine but following an adverse event he was prescribed Aripiprazole. He improved over the course of 6 weeks and has been abstaining from inhalants since 3 months.